2002
DOI: 10.1002/bmc.189
|View full text |Cite
|
Sign up to set email alerts
|

Rapid HPLC measurement of buflomedil in plasma in poisoning cases

Abstract: A rapid high-performance liquid chromatographic method for the determination of buflomedil in human plasma is described. It requires a single liquid-liquid extraction step from 1 mL of plasma with diethyl ether followed by chromatography on a Nova Pak C(18) reversed-phase column and detection by ultaviolet light. Metoclopramide was used as internal standard. The method is sensitive with a quantification limit at 500 ng/mL. It was used for the determination of buflomedil in biological fluids in poisoning cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Previously published methods revealed that the analysis of clonazepam in biological and pharmaceutical samples is vitally important . Thus, several methods have been reported for the determination of this drug, including liquid–liquid extraction and SPE techniques , GC , HPLC with MS and GC–MS , and electrochemiluminescence techniques .…”
Section: Introductionmentioning
confidence: 99%
“…Previously published methods revealed that the analysis of clonazepam in biological and pharmaceutical samples is vitally important . Thus, several methods have been reported for the determination of this drug, including liquid–liquid extraction and SPE techniques , GC , HPLC with MS and GC–MS , and electrochemiluminescence techniques .…”
Section: Introductionmentioning
confidence: 99%
“…There have been few reports for its determination in formulation and in biological fluids using gas chromatography [2][3][4], highperformance liquid chromatography [5][6][7] and reversed-phase ionpair high-performance liquid chromatography [8,9] which mainly concerned with poising or toxicological cases. Therefore, only few methods were determined of BFM in presence of its degradation products.…”
Section: Introductionmentioning
confidence: 99%